2016
DOI: 10.1044/2015_jslhr-s-14-0237
|View full text |Cite
|
Sign up to set email alerts
|

Relations Among Detection of Syllable Stress, Speech Abnormalities, and Communicative Ability in Adults With Autism Spectrum Disorders

Abstract: 2 AbstractPurpose: To date the literature on perception of affective, pragmatic and grammatical prosody abilities in autism spectrum disorders (ASD) has been sparse and contradictory. Interestingly, the primary perception of syllable stress within the word structure, which is crucial for all prosody functions, remains relatively unexplored in ASD. Thus, the current study explored syllable stress perception sensitivity and its relation to speech production abnormalities and communicative ability in adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…Lexical stress is just one type of expressive prosody. With regard to the production of lexical stress, specifically, some previous studies have reported atypical production in ASD (Kargas, López, Morris, & Reddy, 2016;McAlpine, Plexico, Plumb, & Cleary, 2014;Paul, Augustyn, Klin, & Volkmar, 2005) while others have not (Shriberg et al, 2001).…”
mentioning
confidence: 99%
“…Lexical stress is just one type of expressive prosody. With regard to the production of lexical stress, specifically, some previous studies have reported atypical production in ASD (Kargas, López, Morris, & Reddy, 2016;McAlpine, Plexico, Plumb, & Cleary, 2014;Paul, Augustyn, Klin, & Volkmar, 2005) while others have not (Shriberg et al, 2001).…”
mentioning
confidence: 99%
“…Moreover, there have been reports that atypical prosody may persist even after other aspects of speech and language have begun to improve (e.g., DeMyer, Barton, DeMyer, Norton, Allen, & Steele, 1973;Simmons & Baltaxe, 1975). With regard to speech production, in particular, some previous research has found evidence of atypical production of lexical stress in individuals with ASD (Kargas, López, Morris, & Reddy, 2016;McAlpine, Plexico, Plumb, & Cleary, 2014;Paul, Augustyn, Klin, & Volkmar, 2005), while other research has not (Shriberg et al, 2001). None of these studies of lexical stress included acoustic analyses.…”
mentioning
confidence: 99%
“…For example, some individuals with autism spectrum disorders (ASD) produce speech which lacks the usual acoustic characteristics which mark particular prosodic features; for example, the difference in duration between stressed and unstressed syllables tends to be smaller in the speech of children with ASD (Paul, Bianchi, Augustyn, Klin, & Volkmar, 2008). These prosodic production deficits extend to perception as well: individuals with ASD tend to have difficulty with the perception of prosodic cues to emotion (Globerson, Amir, Kishon-Rabin, & Golan, 2015;Golan, Baron-Cohen, Hill, & Rutherford, 2007;Kleinman, Marciano, & Ault, 2001;Phillip et al, 2010;Rutherford, Baron-Cohen, & Wheelwright, 2002), lexical stress (Kargas, López, Morris, & Reddy, 2016), phrase boundaries (Diehl, Bennetto, Watson, Gunlogson, & McDonough, 2008), and linguistic focus (Peppé, Cleland, Gibbon, O'Hare, & Castilla, 2011) in speech (but see Diehl, Friedberg, Paul, & Snedeker, 2015). These prosody perception difficulties can interfere not only with communication skill and sociability (Paul, Augustyn, Klin, & Volkmar, 2005), but may also increase the risk of delayed language acquisition given the importance of prosody for disambiguating language meaning (Lyons, Simmons, & Streeter, 2014).…”
Section: Prosody and Language Acquisitionmentioning
confidence: 99%